EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DALAM MENINGKATKAN PEMBANGUNAN DESA DI DESA RANTAU RASAU II KECAMATAN RANTAU RASAU KABUPATEN TANJUNG JABUNG TIMUR: Mengukur Efektivitas Pengelolaan Dana Desa dalam Mendorong Pembangunan Di Desa Rantau Rasau II - Widiawati, Lusiana (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This research aims to examine and identify the impact of financial ratios, including Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest and Taxes to Total Assets, and Book Value of Equity to Total Liabilities, in predicting corporate financial distress during and after the Covid-19 pandemic. This research is a case study on 27 companies in the Transportation and Logistics sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024, selected through purposive sampling. The data used are secondary financial reports obtained from the IDX website. The analysis was carried out by calculating financial ratios using the Modified Altman Z”-Score model to assess the bankruptcy potential of the companies during the specified period. Based on the analysis results, only the variable Working Capital to Total Assets (WCTA) does not have a significant effect on Financial Distress (FD). Meanwhile, the variables Retained Earnings to Total Assets (RETA), Earnings Before Interest and Tax to Total Assets (EBITTA), and Book Value of Equity to Total Liabilities (BVETL) have a significant effect on Financial Distress (FD).